#TITLE_ALTERNATIVE# - AGUS TRIASMONO (NIM 12103019); Pembimbing : Prof. Dr. Ir. Arief Sudarsono, M.Sc.,
In the mineral processing, both concentrate and tailing are in slurry form. Slurry handling is required, especially related to the transportation. Viscosity is one of parameters which explains about rheology of slurry. By knowing the relation between solid content (%wt), particle size, pH, temperature and viscosity, the controlled variable can be defined easier. Viscosity measurement with Fann VG viscometer shows that solid content, particle size, and temperature influences the viscosity whilst variation pH does not influence the slurry's viscosity. The measured viscosity is used for the measurement of energy required for slurry flowing . The measurement shows that a 40 wt%, -200 mesh, pH 6,49, and temperature 930C is the most favourable condition in term of energy consumption which requires only 2.768,79 kWh per 1 wt%.